CNS small vessel disease: A clinical review. (11th June 2019) - Cannistraro, Rocco J.; Badi, Mohammed; Eidelman, Benjamin H.; Dickson, Dennis W.; Middlebrooks, Erik H.; Meschia, James F.
Abstract : CNS small vessel disease (CSVD) causes 25% of strokes and contributes to 45% of dementia cases. Prevalence increases with age, affecting about 5% of people aged 50 years to almost 100% of people older than 90 years. Known causes and risk factors include age, hypertension, branch atheromatous disease, cerebral amyloid angiopathy, radiation exposure, immune-mediated vasculitides, certain infections, and several genetic diseases. CSVD can be asymptomatic; however, depending on location, lesions can cause mild cognitive dysfunction, dementia, mood disorders, motor and gait dysfunction, and urinary incontinence. CSVD is diagnosed on the basis of brain imaging biomarkers, including recent small subcortical infarcts, white matter hyperintensities, lacunes, cerebral microbleeds, enlarged perivascular spaces, and cerebral atrophy. Advanced imaging modalities can detect signs of disease even earlier than current standard imaging techniques. Diffusion tensor imaging can identify altered white matter connectivity, and blood oxygenation level-dependent imaging can identify decreased vascular reactivity. Pathogenesis is thought to begin with an etiologically specific insult, with or without genetic predisposition, which results in dysfunction of the neurovascular unit. Uncertainties regarding pathogenesis have delayed development of effective treatment. The most widely accepted approach to treatment is to intensively control well-established vascular risk factors, of which hypertension is the most important. With better understanding of pathogenesis, specific therapies may emerge. Early identification of pathologic characteristics with advanced imaging provides an opportunity to forestall progression before emergence of symptoms.